ANTESEDEN DAN KONSEKUENSI TINGKAT PENGUNGKAPAN INFORMASI KEUANGAN BERBASIS INTERNET: PERAN MODERASI KINERJA KEUANGAN - Monica Handoko; Fuad Fuad (Diponegoro Journal of Accounting, 2013)
The rapid development of the Internet led to the emergence of a new means for the company to disclose information to shareholders. Companies can use the internet to disclose financial information to investors. This method is commonly called Internet Financial Reporting (IFR). IFR helps companies to reduce agency costs such as printing and delivery of the financial statements. IFR help companies to disseminate information of positive signals to attract investors. This study aims to analyze the factors influencing the level of disclosure of IFR, the influence of financial performance under moderate the relationship between the level of disclosure IFR and antecedents IFR and relevance of IFR for making decision of investors. The sample of this research is that companies listed on the Indonesia Stock Exchange in 2011. This study used purposive sampling method. The method of analysis used is multiple regression analysis.The results showed that company size, liquidity, company type, distribution of ownership, age listings and earnings per share effect on the level of disclosure IFR. Test results for moderating variables indicate that financial performance affects the relationship between the level of disclosure IFR and antecedents IFR. The test results for outcome variables showed that IFR relevant to making decision investor.